Understanding Digital Natives Learning Experience through Japanese Language Exam at Nihongo Tesuto Bunkasai Competition by PGBJ Jabodetabek in 2023 - Julita Fahrul Rochim; Reza Ilyasa; Nur Ainih (Universitas Muhammadiyah Yogyakarta, 2024)
Integrating technology into Japanese language education has revolutionized the methods of instruction and learning. Especially while instructing the present generation known as digital natives. Educational institutions need to incorporate technology as a tool for teaching and learning due to the close relationship between digital natives and technology. This research aims to assess the utilization of the web-based test (SHIGURU) during the 2023 Bunkasai events organized by PGBJ-SMK (Forum of Japanese Language Teachers for Vocational High Schools) within the area of Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi). This study employs a descriptive research methodology that incorporates both quantitative and qualitative approaches. Data can be collected through direct observation, questionnaires, and interviews. The study utilized primary and secondary data sources, which were examined through triangulation procedures. This study examines the benefits and drawbacks of utilizing shiguru and delves into a comprehensive comprehension of how the digital generation acquires knowledge and how Japanese language education should incorporate pedagogical principles and practices to cater to the requirements of digital natives in contemporary Japanese language education.